The Interaction between Higher Education Institutions and Professional Bodies in the Context of Digital Transformation: The Case of Brazilian Accountants - Bonzanini, Osmar António (2021)
The business economy experienced major changes during the last three decades. The social and economic globalization associated with the fourth revolution put the accounting profession under great pressure toward harmonization and convergence. Still, the route to become a qualified professional accountant varies from country to country all over the world. This paper seeks to understand the evolution of the accounting profession in Brazil and focus on the interaction between higher education institutions (HEIs) and professional bodies, in the context of digital transformation. It is an exploratory study. A survey questionnaire was used to collect data about the perception of the directors of first-degree programs regarding the autonomy of HEIs in defining the curricular contents intended to qualify accounting professionals. The findings show that HEIs are highly influenced by the professional order and Ministry of Education. The limitation associated with this research is that it focusses on one particular professional group in one country.